An access model under cloud computing environment. (8th May 2020) - Gu, Wen; Yang, Cao; Yi, Ying
Concepts such as virtualisation, elasticity, and multi-tenancy have been embedded in cloud computing environments. Thus, the traditional access control model is no longer applicable to cloud computing environments, and designing a new access control model specific to the features of cloud computing environments is necessary. The software as a service (SaaS) pattern has gradually emerged as a type of cloud computing model that can address the information management requirements of small- and medium-sized enterprises. Given the features of SaaS application platforms, this study proposes a multi-tenant access control model called ST-RBAC under the SaaS pattern on the basis of a discussion of the current situation of access control models. The proposed model successfully deals with relationships among elements such as tenants, users, roles, and permissions. Hence, it can effectively guarantee user data safety and user permission management.